Sirtuin 1 in Endothelial Dysfunction and Cardiovascular Aging - Ministrini, Stefano; Puspitasari, Yustina M.; Beer, Georgia; Liberale, Luca; Montecucco, Fabrizio; Camici, Giovanni G. (Frontiers in Physiology, 2021)
Sirtuin 1 (SIRT1) is a histone deacetylase belonging to the family of Sirtuins, a class of nicotinamide adenine dinucleotide (NAD+)-dependent enzymes with multiple metabolic functions. Sirt1 localizes in the nucleus and cytoplasm, and is implicated in the regulation of cell survival in response to several stimuli, including metabolic ones. The expression of Sirt1 is associated with lifespan and is reduced with aging both in animal models and in humans, where the lack of SIRT1 is regarded as a potential mediator of age-related cardiovascular diseases. In this review, we will summarize the extensive evidence linking SIRT1 functional and quantitative defects to cellular senescence and aging, with particular regard to their role in determining endothelial dysfunction and consequent cardiovascular diseases. Ultimately, we outline the translational perspectives for this topic, in order to highlight the missing evidence and the future research steps.